Preparedness of Malaysian pre-school educators for environmental education - Mat Said, Aini; Paim, Laily (Universiti Putra Malaysia Press, 2010)
The shaping of attitude and values, commitment and skills needed to preserve and protect the environment of individuals begins at an early age. Hence educators especially pre-school teachers play an influential role in developing new patterns of behaviors of the young to adopt a sustainable lifestyle. A study was conducted to assess the level of preparedness of the pre-school teachers in Malaysia with respect to their degree of concern for environmental issues, comprehension of fundamental environmental knowledge, and level of adoption of sustainability practices. A cross-sectional research design utilizing survey method was conducted among 300 pre-school teachers representing three different types of pre-schools in Malaysia. Data indicated that the respondents were aware of various basic environmental problems faced by the country but less of the advanced environmental issues. They were found to be more concerned regarding other social problems as compared to environmental ones and adoption of sustainable consumption practices of respondents was modest. Comprehension on fundamental concepts of environment and sustainability needs to be enhanced further through formal training as the main source of environmental knowledge was acquired through the mass media. The study shows that it is imperative for various stakeholders, in particular the Ministry of Education, to develop suitable environmental education syllabus for pre-school teachers training and in-service training programs in order to enhance their preparedness for environmental education.